Avaliação da participação da autofagia de células hospedeiras durante a infecção experimental por Trypanosoma cruzi - Thabata Lopes Alberto Duque (2013)
Chagas disease is caused by the intracellular protozoan parasite Trypanosoma cruzi. It remains a serious public health problem in Latin America, and the current treatment is not satisfactory. The disease morbidity is associated with cardiomyopathy, characterized by tissue damage, inflammatory infiltrates and fibrosis. Parasite internalization and its subsequent success in infection depend on the fusion of the parasitophorous vacuole (PV) to the lysosome, an important organelle related to endocytosis and autophagy. The autophagic pathway is the process involved in degradation of macromolecules and organelles. This pathway was recently associated with T. cruzi infection, but its effective participation as well as its functional role during the infection remain to be defined. Thus, this work aimed to evaluate the occurrence and role of autophagy of macrophages and heart muscle cells (HMC) during the T. cruzi infection. Pre-incubation with autophagic inducers (rapamycin and starvation medium DMEM -/-) reduced infection and endocytic index in both cells, while incubation after infection decreased the parasite replication only in HMC. Ultrastructural analyses of cells previously stimulated with rapamycin and DMEM -/-revealed typical autophagic features such as autophagosomes and concentric membranes. PV- autophagosomes association, suggestive of xenophagy, was also observed. Time- and cell-dependent increase in the autophagic protein LC3 was detected by immunofluorescence after autophagic induction. Immunonanogold electron microscopy showed an i ncrease in this protein expression after infection within autophagosomes. The cross-talk between autophagic pathway and lipid body biogenesis (important inflammatory organelles during infection) indicated a cell-dependent modulation. In conclusion, autophagy was characterized as an important process in response to the T. cruzi infection and seems to participate in the host resistance acting in the control of the infection in macrophages and cardiac cells.